2019
DOI: 10.1140/epjc/s10052-019-6941-y
|View full text |Cite
|
Sign up to set email alerts
|

D-dependence of the gap between the critical temperatures in the one-dimensional gauge theories

Abstract: We investigate the dimensional dependence (D-dependence) of the difference (gap) between the critical temperatures associated with the uniform/non-uniform and non-uniform/gapped transitions in the large-N bosonic gauge theories with D matrix scalar fields on a S 1 -circled space. We use the equations describing these critical temperatures given in the 1/D expansion [1]. These transitions are related with Gregory-Laflamme instabilities in the gravities and Rayleigh-Plateau instabilities in the fluid dynamics, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
(215 reference statements)
0
2
1
Order By: Relevance
“…Our results are in a broad agreement with 1/D studies [17,25] but does not match it exactly as the authors observe two closely separated phase transitions. As a recent numerical study of the BFSS model [18] also reports a single phase transition, we believe that by including higher terms in the 1/D expansion, the two phase transitions would merge into a single one in this approximation as well.…”
Section: Discussioncontrasting
confidence: 48%
“…Our results are in a broad agreement with 1/D studies [17,25] but does not match it exactly as the authors observe two closely separated phase transitions. As a recent numerical study of the BFSS model [18] also reports a single phase transition, we believe that by including higher terms in the 1/D expansion, the two phase transitions would merge into a single one in this approximation as well.…”
Section: Discussioncontrasting
confidence: 48%
“…For the case with µ = 0, known as the bosonic BFSS model, there are already several studies in the literature. These include a perturbative expansion in 1/D [14,16,30], where D is the number of matrices (D = 9 in our case), and numerical studies [13][14][15]17]. Both the 1/D expansion [16] and earlier studies [13] reported two closely separated critical tem-JHEP06(2020)174…”
Section: ) Andmentioning
confidence: 82%
“…A straightforward calculation [6,7,28] shows that, in the large-N limit, there is a single phase transition with critical temperature T c = For the case with µ = 0, known as the bosonic BFSS model, there are already several studies in the literature. These include a perturbative expansion in 1/D [14,16,29], where D is the number of matrices (D = 9 in our case), and numerical studies [13,14,17]. Both the 1/D expansion [16] and earlier studies [13] reported two closely separated critical temperatures.…”
Section: The Model and Observablesmentioning
confidence: 87%